Design and partial-load operation of a reversible Solid Oxide Cell system with molten salts thermal storage. Issue 1 (1st December 2022) - Ficili, Marco; Colbertaldo, Paolo; Guandalini, Giulio; Campanari, Stefano
Abstract: The increasing penetration of renewable energy sources in the electricity mix requires efficient storage solutions on the seasonal scale. Reversible Solid Oxide Cell (rSOC) systems are receiving increased attention as viable options to fulfil this requirement. In this work, a MW-scale rSOC system capable of working over a large operating window is studied via modelling on Aspen Plus®. To ease the thermal integration, a molten salt thermal storage is coupled to the system, enabling heat recovery in fuel cell mode, which is then exploited for water evaporation in electrolysis mode. The rSOC stack is designed to operate exothermically in the electrolysis mode at nominal load. In both modalities, the air mass flow rate is regulated to control the stack temperature, while limiting the in-out gradients within 100°C. At nominal load, the system achieves an electrical efficiency of 52% in fuel cell mode and of 87% in electrolysis mode. The operation at low partial loads, due to the decrease of the air flow rate, requires an additional high-temperature heat source to guarantee the heat integration. In this regard, the adoption of an electrical resistance in electrolysis mode and a hydrogen-fed combustor in fuel cell mode are selected as viable solutions to amplify the operating range of the system. As a results, the system can be operated down to the 30% of the stack nominal power in both modalities, where the system achieves an electric efficiency of 44% and 80% in fuel cell and electrolysis mode, respectively.